2017
DOI: 10.3390/ma10050563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Exposure on Mechanical and Tribological Behavior of CrxN Coatings Deposited at Different Pressures on IN718

Abstract: In the current study, the properties of the CrxN coatings deposited on the Inconel 718 superalloy using direct current reactive magnetron sputtering are investigated. The influence of working pressure on the microstructure, mechanical, and tribological properties of the CrxN coatings before and after high-temperature hydrogen exposure is studied. The cross-sectional scanning electron micrographs indicate the columnar structure of the coatings, which changes from dense and compact columns to large columns with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
(58 reference statements)
1
13
0
Order By: Relevance
“…Additionally, the (110) peak of Cr 2 O 3 oxide phase was detected that probably was associated with the formation of the thin oxide layer on the surface during cooling of the sample after hydrogenation. Similar to our previous work, the lowest hydrogen absorption was found for the coating with mixed hcp-Cr 2 N and c-CrN phase composition due to the higher packing density of the cubic structure [13]. Zhou et al [43] observed for titanium nitride coatings that hydrogen impermeability of the coating also depends on the crystal orientation of the films.…”
Section: Crystalline Structuresupporting
confidence: 73%
See 4 more Smart Citations
“…Additionally, the (110) peak of Cr 2 O 3 oxide phase was detected that probably was associated with the formation of the thin oxide layer on the surface during cooling of the sample after hydrogenation. Similar to our previous work, the lowest hydrogen absorption was found for the coating with mixed hcp-Cr 2 N and c-CrN phase composition due to the higher packing density of the cubic structure [13]. Zhou et al [43] observed for titanium nitride coatings that hydrogen impermeability of the coating also depends on the crystal orientation of the films.…”
Section: Crystalline Structuresupporting
confidence: 73%
“…The difference in hydrogen absorption is associated with the modification of crystalline structure and morphology of the coatings. On the one hand, the formation of mixed CrN + Cr2N phase in coatings deposited at 60 V leads to lower hydrogen permeation through the coating than the Cr2N phase formed at higher bias voltages [13,18,25]. On the other hand, the denser structure of the coatings deposited at higher bias voltages reduces the rate of hydrogen diffusion through the coating due to reduced intergranular space and pores in the coating.…”
Section: Crystalline Structurementioning
confidence: 96%
See 3 more Smart Citations